Optimization of the Selective Monohydrolysis of Diethyl 4-Aryl-4H-pyran-3,5-dicarboxylates - Hong Yan; Xiuqing Song; Xiaohui Song; Jiaojiao Duan (Molecules, 2011)
A simple, efficient and eco-friendly procedure for the selective monohydrolysis of diethyl 2,6-dimethyl-4-aryl-4H-pyran-3,5-dicarboxylates under quaternary ammonium salt catalysis conditions is presented. The catalytic activities of various quaternary ammonium salts were investigated using different molar ratios of NaOH and water-organic solvent mixtures. The results indicate that the combination of 1.0 equivalent of tetraethyl-ammonium bromide (TEAB) with 1.2 equivalents of NaOH in a 10% water-ethanol media at 40 °C displays remarkable selectivity for the monohydrolysis of diethyl 2,6-dimethyl-4-aryl-4H-pyran-3,5-dicarboxylates. The utility of this process is demonstrated by the monohydrolysis of a series of 4-aryl-4H-pyran-3,5-dicarboxylate esters to afford the corresponding monoesters in 20–80% yields under the optimized conditions.